Analisis Determinan Pertumbuhan Ekonomi IMT-GT Periode Tahun 2000-2021 - Aula Maulidah; Yusrizal Yusrizal; Khairina Tambunan (STIKes Ibnu Sina Ajibarang, 2023)
This research aims to analyze FDI, Exports, and Inflation on the Determinants of Economic Growth IMT-Gt for the 2000-2021 Period. This research uses a quantitative approach with panel data for 22 years. This research uses secondary data obtained from the World Bank. The analytical tool used in this research is SPSS 23 with multiple regression analysis techniques. The research results show that the partial FDI variable has no effect on Indonesia, Malaysia and Thailand. The partial inflation variable has no effect on Indonesia and Thailand. In Malaysia, the inflation variable is significant. Meanwhile, partially the Export variable has a significant impact on the Economic Growth of Indonesia, Malaysia and Thailand. Simultaneous research on the variables FDI, Exports and Inflation influence the Economic Growth of Indonesia, Malaysia and Thailand.